2022
DOI: 10.1017/bca.2021.14
|View full text |Cite
|
Sign up to set email alerts
|

Demand for an Environmental Public Good in the Time of COVID-19: A Statewide Water Quality Referendum

Abstract: Due to COVID-19, many households faced hardships in the spring of 2020 – unemployment, an uncertain economic future, forced separation, and more. At the same time, the number of people who participated in outdoor recreation in many areas increased, as it was one of the few activities still permitted. How these experiences affect the public’s willingness to pay (WTP) for environmental public goods is unknown. During the early months of the pandemic, we conducted a stated preference survey to value statewide wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…A number of other studies have suggested a relationship between human health and the environment, and examined the importance of the surrounding environment and satisfaction with the residential area from a mental health perspective (Anessi-Pessina et al, 2020;Tracker, 2020;Dzigbede et al, 2020). Moreover, many studies have been conducted on approaches to improving environmental quality, including studies estimating the willingness to pay (WTP) for improved water services using the contingent valuation method (Galarza Arellano, 2023;Parsons et al, 2022;Catma and Varo, 2021), or estimating the WTP for better air quality and examining the factors affecting the public's WTP (Malik et al, 2022;Jiang et al, 2024;Song et al, 2021) Therefore, the purpose of this study is to examine the satisfaction of Taean-gun residents with each environmental sector and whether their environmental concerns have changed due to the COVID-19 pandemic, and to determine the willingness to pay for environmental improvement and the determinants that affect the willingness to pay. In this study, frequency analysis, cross-tabulation analysis, and logit analysis were performed based on a survey conducted in 2020, during the COVID-19 period.…”
mentioning
confidence: 99%
“…A number of other studies have suggested a relationship between human health and the environment, and examined the importance of the surrounding environment and satisfaction with the residential area from a mental health perspective (Anessi-Pessina et al, 2020;Tracker, 2020;Dzigbede et al, 2020). Moreover, many studies have been conducted on approaches to improving environmental quality, including studies estimating the willingness to pay (WTP) for improved water services using the contingent valuation method (Galarza Arellano, 2023;Parsons et al, 2022;Catma and Varo, 2021), or estimating the WTP for better air quality and examining the factors affecting the public's WTP (Malik et al, 2022;Jiang et al, 2024;Song et al, 2021) Therefore, the purpose of this study is to examine the satisfaction of Taean-gun residents with each environmental sector and whether their environmental concerns have changed due to the COVID-19 pandemic, and to determine the willingness to pay for environmental improvement and the determinants that affect the willingness to pay. In this study, frequency analysis, cross-tabulation analysis, and logit analysis were performed based on a survey conducted in 2020, during the COVID-19 period.…”
mentioning
confidence: 99%